الرضا الوظيفى المحدد و الرضا الوظيفى المطلق لدى مستشاري التوجيه المهني في ضوء بعض المتغيرات الديمغرافية - زقرير الحاج محمد عبد القادر الكبير; حشاني سارة حفيظة; محمد بوفاتح (My University, 2023)
The current study aimed at identifying the level of absolute job satisfaction and job satisfaction identified by guidance and counseling counselors in vocational training centers in Laghouat using the analytical descriptive curriculum as the appropriate curriculum for such studies. The functional satisfaction scale was applied to a sample of 10 advisers, the results of which showed the following: -Decrease in the level of absolute job satisfaction among study sample members -Reduced level of job satisfaction identified by study sample members -There is a positive correlation between absolute and specific job consent. Keywords: absolute job satisfaction, specific job satisfaction, guidance and guidance advisers